2015
DOI: 10.1111/hae.12748
|View full text |Cite
|
Sign up to set email alerts
|

Distress in patients with bleeding disorders: a single institutional cross‐sectional study

Abstract: Distress among patients with congenital bleeding disorders followed at a comprehensive HTC was high and similar to that reported among patients with cancer. Future research should determine whether distress impacts clinical outcomes in patients with bleeding disorders as demonstrated in other chronic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 31 publications
4
43
0
Order By: Relevance
“…In this study, the association between professional status and both anxiety and depression remained significant even after controlling for clinical variables (disease severity and number of affected joints), showing that unoccupied patients (unemployed, retired or on medical leave) present higher symptomatology. These findings add to previous conclusions regarding PWH, providing a research direction on the impact of haemophilia on emotional well‐being and underscoring the relevance of a biopsychosocial model of haemophilia care that also considers professional status as a potential risk factor for poor mental health. Although further research is warranted, it can be suggested that PWH would benefit from more flexible employment policies.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In this study, the association between professional status and both anxiety and depression remained significant even after controlling for clinical variables (disease severity and number of affected joints), showing that unoccupied patients (unemployed, retired or on medical leave) present higher symptomatology. These findings add to previous conclusions regarding PWH, providing a research direction on the impact of haemophilia on emotional well‐being and underscoring the relevance of a biopsychosocial model of haemophilia care that also considers professional status as a potential risk factor for poor mental health. Although further research is warranted, it can be suggested that PWH would benefit from more flexible employment policies.…”
Section: Discussionsupporting
confidence: 75%
“…Pain is a central issue in haemophilia care, either due to haemarthrosis or to chronic arthropathy, which has been associated with higher emotional distress . Congruently in this study, participants with significant anxiety/depression symptoms were more likely to report higher pain frequency, with heightened intensity and interference.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…24 A person with haemophilia may experience sporadic or persistent distress related to their disease which may impact their ability to cope with and manage health. 24 A person with haemophilia may experience sporadic or persistent distress related to their disease which may impact their ability to cope with and manage health.…”
Section: Introductionmentioning
confidence: 99%